Popular Culture in the Arab World arts, politics, and the media - Hammond, Andrew 1970- (The American University in Cairo Press, 2007)
"Over the last fifty years the Arab world has witnessed two seemingly contradictory trends: governments have failed to unite the region politically, but at the same time a vibrant popular culture has blossomed, strengthening the sense of a shared Arab identity. Egyptian soap operas, Arab pop stars, al-Jazeera television, Islamic televangelists, and a raging debate over the 'war on terror' and the future of the Arabs are just some of the phenomena that make up the immensely rich and diverse world of the Arab mass media." "Looking at such diverse cultural forms as commercial cinema, pop music, television, theater, and popular religion, journalist Andrew Hammond portrays the lively popular culture of the region in a refreshing antidote to stereotypical views about the Middle East. From Lebanese pop sensation Nancy Ajram to Shaaban Abdel-Rahim, an illiterate ironer of clothes in Cairo who rose to stardom singing of his support for Palestinians against Israel, this unique book highlights the unlikely heroes of Arabism."--Book cover.